2020
DOI: 10.4314/jasem.v24i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Wound Healing Activity of Green Synthesized Titanium Oxide Nanoparticles using <i>Strychnos spinosa </i>and <i>Blighia sapida</i>

Abstract: The biosynthesis of nanoparticles has been proposed as a cost effective and environmentally friendly alternative to chemical and physical methods. The present work investigates the synthesis of titanium oxide nanoparticles (TiO2 NPs) by green approach using Strychnos spinosa and Blighia sapida leave extracts. The detailed characterization of the TiO2 NPs was carried out using UV-Visible Spectroscopy, Scanning Electron Microscopy (SEM), X- ray Diffraction (XRD), and Fourier-Transform Infrared (FTIR) Spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The nanoparticles effectively reduced wound size more significantly than the control group, indicating efficient wound healing progression [ 56 ]. A reflection of the TiNPs’ strong antibacterial potentials, as demonstrated by the findings of the in vivo and in vitro antibacterial assays, is the absence of irritation and/or discomfort at the wound site during treatment and the considerable acceleration of wound contraction and re-epithelialisation rates, primarily seen in the remodelling phase of wound healing [ 59 ].…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…The nanoparticles effectively reduced wound size more significantly than the control group, indicating efficient wound healing progression [ 56 ]. A reflection of the TiNPs’ strong antibacterial potentials, as demonstrated by the findings of the in vivo and in vitro antibacterial assays, is the absence of irritation and/or discomfort at the wound site during treatment and the considerable acceleration of wound contraction and re-epithelialisation rates, primarily seen in the remodelling phase of wound healing [ 59 ].…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…When formulated as nanoparticles, the extract has a higher surface area to volume ratio. Nanostructures give pharmacological agents a distinct advantage, contributing to improved pharmacological effects [70]. When HU extract is prepared as a nanoparticle, the chances of interactions with the wound surface and permeation into the wound site are increased.…”
Section: Wound Healing Studiesmentioning
confidence: 99%
“…(Seydi et al, 2019a), Allium eriophyllum Boiss (Seydi et al, 2019b) found to be excellent antibacterial agent against S. aureus. Hassan et al (2020) fabricated TiO2NPs using Strychnos spinosa and Blighia sapida leave extracts. The phytofabricated TiO2NPs exhibited wound healing property by decreasing S. aureus load in albino rat.…”
Section: Titanium Nanoparticlesmentioning
confidence: 99%